2019
DOI: 10.1016/j.addr.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic changes in cancer and drug delivery to the lymphatics in solid tumors

Abstract: Although many solid tumors use the lymphatic system to metastasize, there are few treatment options that directly target cancer present in the lymphatic system, and those that do are highly invasive, uncomfortable, and/or have limitations. This review gives a brief overview of lymphatic function and anatomy, discusses changes that befall the lymphatics in cancer and the mechanisms by which these changes occur, and presents limitations for drug delivery to the lymphatic system. We then go on to summarize releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 179 publications
(335 reference statements)
1
35
0
1
Order By: Relevance
“…Meanwhile, with the increase of the particle size of PLGA NPs, their brain accumulation efficiency gradually decreased, which was only 6.0% for 131 nm PLGA NPs and 3.8% for 181 nm PLGA NPs (P. Zhao et al, 2020). These results corroborate with previous reports that the transport of NPs to lymph node was strictly limited by the size‐restriction of the lymph node reticular network (Cote et al, 2019; Mei et al, 2018) and the size of NPs (L. X. Zhang et al, 2018). Therefore, the appropriate physical properties (such as particle size) should be taken into consideration for improved brain accumulation efficiency under the SC‐route.…”
Section: Ad Targeted Delivery Of Nanomedicinessupporting
confidence: 92%
“…Meanwhile, with the increase of the particle size of PLGA NPs, their brain accumulation efficiency gradually decreased, which was only 6.0% for 131 nm PLGA NPs and 3.8% for 181 nm PLGA NPs (P. Zhao et al, 2020). These results corroborate with previous reports that the transport of NPs to lymph node was strictly limited by the size‐restriction of the lymph node reticular network (Cote et al, 2019; Mei et al, 2018) and the size of NPs (L. X. Zhang et al, 2018). Therefore, the appropriate physical properties (such as particle size) should be taken into consideration for improved brain accumulation efficiency under the SC‐route.…”
Section: Ad Targeted Delivery Of Nanomedicinessupporting
confidence: 92%
“…That study’s findings are further strong evidence that the lymphatic system is a major pathway for cancer metastasis. These findings also suggest that studies on lymphatic targeting and migration of anticancer drugs are crucial, and, in fact, researchers have studied a number of targeting strategies and benefits based on the structural and physiological characteristics of the lymphatic system related to drug delivery [ 6 , 7 , 8 , 9 ]. Researchers have also reported on improving bioavailability and efficacy through formulations of conventional drugs [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that intradermal injection can lead to a localized increase in interstitial pressure within the dermis, potentially increasing the rate of ICG drainage and interfering with measurements [26,27]. A proposed solution to this issue has been the delivery of ICG using microneedles (MNs) [28].…”
Section: Introductionmentioning
confidence: 99%